Castleman’s disease: a diagnostic and therapeutic quandary, case series from a tertiary cancer centre in South - Saxena, Sachet; Anand, Nitesh; Nandennaver, Manjunath; Karpurmath, Shashidhar V.; Angadi, Veerendra; L., Shilpa (International Journal of Research in Medical Sciences, 2025)
Castleman’s disease (CD) is a rare, nonclonal lymphoproliferative disorder which was first described by Dr Benjamin Castleman. It can affect lymph nodes of any part of body, imitating both benign and malignant diseases. Co-occurrence and overlap in significant number of cases can be seen with lymphomas, amyloidosis and POEMS syndrome making its diagnosis and treatment challenging. We present a case series of four cases of CD, registered from January 2017 to August 2024.The mean age of presentation was 27 (13 - 42) years. There was male preponderance in the study with male to female ratio of 3:1. All the patients were immunocompetent. One patient belonged to pediatric age group where as other three were adults. Two patient was initially misdiagnosed out of which one received erroneous treatment for tuberculosis. In patients with multicentric CD, one was diagnosed with POEMS syndrome. Complete surgical excision was offered for unicentric CD. All the multicentric CD patients were treated with chemotherapy +/- immunotherapy. All the patients were alive on last follow up. Castleman’s disease is a rare disease having outcomes ranging from a benign to potentially fatal course. CD possesses a diagnostic challenge, as lack of specific features makes it difficult to distinguish it from other diseases often leading to inaccurate diagnosis and superfluous treatment. POEMS syndrome is frequently associated with CD. Surgical excision remains the mainstay treatment for unicentric CD, whereas patients with multicentric disease chemoimmunotherapy remains an acceptable option however owing to multiple complexities and association with other concomitant diseases, the overall prognosis of MCD remains abysmal.